The Effect of Hemodialysis Adequacy on Inflammatory Status in Stage 5 Chronic Kidney Disease Patients - Dedi Winarto; Dwi Lestari Partiningrum; Lestariningsih Lestariningsih; Ayudyah Nurani; Arwedi Arwanto; Shofa Chasani (PERNEFRI (PERHIMPUNAN NEFROLOGI INDONESIA), 2025)
Background: Chronic Kidney Disease (CKD) is a critical global health issue, particularly Stage 5 CKD, where kidney function is severely impaired. Hemodialysis, essential for managing such patients, aims to remove waste and excess fluids. Chronic inflammation, common among CKD5-HD patients, heightens cardiovascular risks and worsens quality of life. Hemodialysis adequacy, measured by the Kt/V ratio, plays a vital role in outcomes, yet its relationship with inflammatory markers, such as Hs-CRP, albumin, and TIBC, remains unclear. Objective: This study aimed to evaluate the relationship between hemodialysis adequacy, as reflected by Kt/V values, and inflammatory markers such as c-reactive protein (CRP), albumin, and total iron binding capacity (TIBC) in CKD stage 5 patients undergoing hemodialysis, providing insights into optimizing dialysis protocols to mitigate inflammation. Methods: A cross-sectional study of 45 CKD5-HD patients assessed Kt/V values and inflammatory markers (Hs-CRP, albumin, TIBC). Data were analyzed using Shapiro-Wilk, Independent t-tests, or Mann-Whitney U tests based on data distribution. Results: The mean Kt/V value was 1.31 ± 0.21. Lower Kt/V values were significantly associated with elevated Hs-CRP levels (p = 0.018). No significant differences in Kt/V values were observed concerning albumin (p = 0.546) or TIBC (p = 0.523). Correlations between Hs-CRP and albumin or TIBC were non-significant (p = 1.000). Conclusion: Adequate hemodialysis, reflected in optimal Kt/V values, is crucial for reducing systemic inflammation marked by Hs-CRP. Albumin and TIBC levels showed no significant association, underscoring the multifactorial nature of inflammation in CKD5 patients.